A motivação como estratégia de aprendizagem da matemática - Morais, Auricelio Carneiro de (Universidade Federal Rural do Semi-Árido, 2020)
The growing lack of interest that many students have in Mathematics, togheter with the gradual increase in learning deficiencies and the difficulty in developing skills and abilities necessary to achieve success in their learning, are problems that are reflected in the low performance of students in external evaluations of Basic Education, and characterize situations that justify the importance and relevance of this research. Motivation as a strategy for mathematics learning is the approach used here to face these problems. Its general objective is to reflect the motivation in the mathematics teaching and learning process, as well as to present proposals for activities based on this conception. With this objective, we seek to make mathematics learning more attractive, proposing the encouragement of students' potential and reflections regarding this process. In addition, it proposes to make teaching material available for teachers to use or adapt for their classes, using the motivation techniques described in the book The Art of Motivating High School Students for Mathematics by the authors Alfred S. Posamentier and Stephen Krulik. Therefore, it was performed a qualitative approach of applied nature with exploratory and descriptive goals using a research action, starting from the theoretical study on motivation in education and strategies used to achieve it, continuing with activities selection, elaboration of application strategies, its execution in the classroom and, finally, the analysis of the students' statements until obtaining the results. Thus, it was observed that the activities proposed using the addressed motivation techniques met the proposed objectives, motivating the students during the activities realization and giving them voice and place, permeating discussions that occurred between the students and the teacher throughout the process, which are registered in the present work through dialogues. This allows us to conclude that the use of activities, based on motivation techniques, made it possible to verify in which level of learning the students are in, as well as the possibility to analyze how they learn, demystifying the idea that only few students have the capacity to understand Mathematics. All of this provided among the students greater motivation for mathematics learning, which is essential and indispensable for the construction of learnig based on the capacity to solve problems, whatever is the situation that requires the individual’s thinking to solve it
Keywords: Matemática; Motivação; Aprendizagem; Atividades; Mathematics; Motivation; Learning; Activitie; CIENCIAS EXATAS E DA TERRA::MATEMATICA